Mitigation and adaptation strategies to offset the impacts of climate change on urban health: A European perspective - Kyprianou, I.; Artopoulos, G.; Bonomolo, A.; Brownlee, T.; Cachado, R.; Camaioni, C.; Đokić, V.; D'Onofrio, R.; Đukanović, Z.; Fasola, S.; Di Giovanni, C.; Grifoni, R. C.; et al. (Building and Environment, 2023)
Climate change threatens urban health, whether that refers to the human or environmental aspects of urban life. At the same time, initiatives of city regeneration are envisioning alternative forms of the urban environment, where derelict spaces have the potential to be brought back to life in ways that would not compromise urban health. Regeneration processes should utilise mitigation and adaptation strategies that consider the future needs and anticipated role of cities within the context of the discourse about climate change, accounting for expected and unforeseen impacts and regarding the city as an agent of action rather than a static territory too complex to change. Nevertheless, literature implicating these three parameters synchronously, namely, climate change, cities, and health, has been scarce. This study aims to fill this gap through a systematic literature review, exploring adaptation and mitigation strategies that can be employed in urban regeneration efforts aiming to mitigate climate change and its impacts on urban health as well as identifying the main trends and opportunities overlooked. Findings show that even though the emphasis is given to the physical actions and impacts of climate change and urban health, an emerging theme is the need to engage civic society in co-designing urban spaces. Synergistic relationships, collaborations and avoidance of lock-in situations appears to be the most significant subtopic emerging from this literature review One main recommendation is to promote a community-driven, inclusive, participatory approach in regeneration projects. This will ensure that different vulnerabilities can be adequately addressed and different population groups will have equitable health benefits.